A novel cDNA, priBc, encoding a protein with a Zn(II)2Cys6 zinc cluster DNA-binding motif, derived from the basidiomycete Lentinus edodes - Endo, Hirofumi; Kajiwara, Susumu; Tsunoka, Osamu; Shishido, Kazuo (Gene, 1994)
A cDNA clone (designated priBc) was isolated from a primordial cDNA library of the basidiomycete, Lentinus edodes ( Le). The priBc clone consisted of 2628 bp encoding 565 amino acids. As was expected, the priB transcript was abundant in primordia, while preprimordial mycelia and mature fruiting bodies contained lower levels of this Le transcript. The deduced PRIB protein (64kDa) contained a ‘Zn(II)2Cys6 zinc cluster’ DNA-binding motif. PRIB was produced in Escherichia coli using the bacteriophage T7 expression system. Southwestern blot analysis revealed that PRIB binds to the DNA fragment containing the upstream region of priB.